Crystal structure, chemical bonding, and electrical and thermal transport in Sc5Rh6Sn18. Issue 20 (7th May 2020) - Feig, Manuel; Akselrud, Lev; Schnelle, Walter; Dyadkin, Vadim; Chernyshov, Dmitry; Ormeci, Alim; Simon, Paul; Leithe-Jasper, Andreas; Gumeniuk, Roman
Abstract : Single crystals of the superconductor Sc5 Rh6 Sn18 were grown from Sn-flux. Abstract : Single crystals of Sc5 Rh6 Sn18 were grown from Sn-flux. The crystal structure (SG: I 41 / acd, a = 13.5529(2) Å, c = 27.0976(7) Å) was studied by high-resolution X-ray diffraction on powder and single crystal material as well as by TEM. All methods confirm it to crystallize with a Sc5 Ir6 Sn18 (space group I 41 / acd ) type structure. The performed structural studies also suggest the presence of local domains with a broken average translational symmetry. An analysis of the chemical bonding situation reveals highly polar covalent Sc2–Sn1, Sn–Rh and Sc2–Rh bonds, two- and three-centre bonds involving Sn-atoms as well as the ionic nature of Sc1 bonding. The thermopower of Sc5 Rh6 Sn18 is isotropic, small and negative ( i.e. dominance of electron-like charge carriers). Due to structural disorder, the thermal conductivity is lower in comparison with regular metallic systems.